1993
DOI: 10.1148/radiology.188.2.8327699
|View full text |Cite
|
Sign up to set email alerts
|

Microcalcifications on postoperative mammograms as an indicator of adequacy of tumor excision.

Abstract: Mammograms, including microfocus spot magnification views, were obtained before reexcision of the tumor-ectomy site in 43 women with breast carcinoma. These studies were prospectively evaluated by radiologists experienced in breast imaging. All women had mammographically evident microcalcifications associated with their original tumors. In all, tumor was at or near the margin of resection or the status of margins was unknown, necessitating reexcision of the tumorectomy site. Of 29 women with residual microcali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…Microcalcifications, formed within areas of high-grade comedonecrosis DCIS and visualized by mammography, can predict the minimum extent of DCIS (actual tumors often extend beyond microcalcifications) with a positive predictive value of 0.9 (18)(19)(20). We used microcalcifications to estimate the extent of disease and confirmed these findings with MRI.…”
Section: Resultsmentioning
confidence: 89%
“…Microcalcifications, formed within areas of high-grade comedonecrosis DCIS and visualized by mammography, can predict the minimum extent of DCIS (actual tumors often extend beyond microcalcifications) with a positive predictive value of 0.9 (18)(19)(20). We used microcalcifications to estimate the extent of disease and confirmed these findings with MRI.…”
Section: Resultsmentioning
confidence: 89%
“…To our knowledge, no clear recommendation exists regarding post-operative mammography before adjuvant radiotherapy except in cases of tumours containing calcifications, when a mammogram should be obtained after surgery to determine whether all calcifications have been removed [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only three other comparable series provide data that directly address the role of postexcision mammography in the setting of DCIS. The first of these was published in 1993 by Gluck et al 17 The authors reported that 10 of 15 (67%) patients with residual calcifications on postoperative mammogram had residual DCIS at re-excision. Unlike the present study, Gluck's series included only patients with positive or unknown margins in whom re-excision of the tumor site already was planned.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] There are few data in the literature about the efficacy of postexcision mammography during the initial treatment of patients with DCIS. [17][18][19] The purpose of this study was to assess the yield and impact of postexcision mammography in the treatment of patients with DCIS.…”
mentioning
confidence: 99%